2021
DOI: 10.1001/jamaophthalmol.2020.6985
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Exposure With Risk of Behçet Disease Among Patients With Uveitis

Abstract: IMPORTANCEAlthough experimental studies support the hypothesis that exposure of infectious agents may trigger an aberrant immune response and contribute to noninfectious uveitis, the association of a definite pathogen with human noninfectious uveitis conditions appears not to have been well established in a population.OBJECTIVE To evaluate associations of tuberculosis infection with risk of several noninfectious uveitis conditions. DESIGN, SETTING, AND PARTICIPANTS These mendelian randomization and observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For example, Campisi et al found that apoptosis of Mtb -infected host cells enabled generation of self-reactive T H 17 cells, a subset of helper T-lymphocytes associated with autoimmune diseases 196 . Zhong et al established that Mtb exposure or genetic susceptibility to TB is a risk factor for uveitis secondary to Behçet disease 197 . Moreover, Previously identified pulmonary TB transcriptomic biomarker signatures were upregulated in HIV positive patients and correlated with viral loads in the absence of TB infection 198 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Campisi et al found that apoptosis of Mtb -infected host cells enabled generation of self-reactive T H 17 cells, a subset of helper T-lymphocytes associated with autoimmune diseases 196 . Zhong et al established that Mtb exposure or genetic susceptibility to TB is a risk factor for uveitis secondary to Behçet disease 197 . Moreover, Previously identified pulmonary TB transcriptomic biomarker signatures were upregulated in HIV positive patients and correlated with viral loads in the absence of TB infection 198 .…”
Section: Discussionmentioning
confidence: 99%
“…25 As we know, Behçet's uveitis is an autoinflammatory disease in which the IL-17/IL-23 pathway is involved 26 and infectious exposure such as tuberculosis may also be a risk factor for Behçet's uveitis. 27 In the early stages of experimental autoimmune uveoretinitis, microglia migrate to the photoreceptor cell layer, where they produce TNF-a and peroxynitrite. 28 This microglial migration and activation occur before macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, Mycobacterium tuberculosis causes inflammatory immune response in the body [ 163 ], but no evidence based on MR analyses have been reported. However, Zhong et al conducted MR and mycobacterium tuberculosis T cell spot test (T-SPOT.TB) analyses and showed that tuberculosis infection increased the risk of several non-infectious uveitis conditions [ 164 ].…”
Section: Mr Ophthalmology Studiesmentioning
confidence: 99%